Catalytic asymmetric acetalization of carboxylic acids for access to chiral phthalidyl ester prodrugs - Liu, Yingguo (2019)
Carboxylic acids are common moieties in medicines. They can be converted to phthalidyl esters as prodrugs. Unfortunately, phthalidyl esters are now mostly prepared in racemic forms. This is not desirable because the two enantiomers of phthalidyl esters likely have different pharmacological effects. Here we address the synthetic challenges in enantioselective modification of carboxylic acids via asymmetric acetalizations. The key reaction step involves asymmetric addition of a carboxylic acid to the catalyst-bound intermediate. This addition step enantioselectively constructs a chiral acetal unit that lead to optically enriched phthalidyl esters. A broad range of carboxylic acids react effectively under mild and transition metal-free conditions. Preliminary bioactivity studies show that the two enantiomers of chlorambucil phthalidyl esters exhibit different anti-cancer activities to inhibit the growth of Hela cells. Our catalytic strategy of asymmetric acetalizations of carboxylic acids shall benefit future development of chiral phthalidyl ester prodrugs and related molecules.